A current sensor fault diagnosis method based on phase angle shift technique applying to induction motor drive - Quang Sy Vu; Cuong Dinh Tran; Bach Hoang Dinh; Chau Si Thien Dong; Hung Tan Huynh; Huy Xuan Phan (Institute of Advanced Engineering and Science, 2022)
An improved method using the phase angle shift characteristic of the sine wave is proposed to diagnose the fault states of the current sensors in an induction motor drive. The induction motor drive (IMD) system applied in this study uses the field-oriented control (FOC) loop with integrated two current sensors and a speed encoder to control the rotor speed. The space vectors created from the phase angle shift technique are compared to the estimated current for the fault diagnosis algorithm. Various types of current sensor failures are investigated by MATLAB/Simulink software to check the effectiveness of the proposed method. The simulation results have proved the performance of the proposed method in enhancing the reliability and stability of the IMD system.